Development and Characterization of Nanostructured Pharmacosomal Mesophases: An Innovative Delivery System for Bioactive Peptides - Maryam Rezvani; Javad Hesari; Seyed Hadi Peighambardoust; Maria Manconi; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2018)
Purpose: To potentially enhance the bioavailability and extend the bioactivity effectiveness of Isoleucine-Proline-Proline (IPP, an antihypertensive bioactive peptide of dairy origin), a novel Lyotropic Liquid Crystalline Pharmacosomal Nanoparticle (LLCPNP) was synthesized, and its physicochemical and technological characteristics were studied. Methods: LLCPNPs precursors were developed using IPP and soy phosphatidylcholine via complex formation. Polarized light microscopy, small angle X-ray scattering, differential scanning calorimetry, dynamic light scattering and Fourier transform infrared spectroscopy were employed to characterize the physicochemical properties of the nanoparticles. The in-vitro release and its related mechanisms were also studied. Results: Fourier transform infrared spectroscopy confirmed the complexation between the components of LLCPNPs. Phase behavior evaluation by polarized light microscope showed the characteristic birefringent texture. These findings along with those of small angle X-ray scattering and differential scanning calorimetry proved the formation of lamellar LLCPNPs. These particles represented nanometric size (<100 nm), high incorporation efficiency (93.72%) and proper physicochemical stability during long-term storage. In-vitro studies demonstrated a sustained release behavior fitted to non-Fickian diffusion and Higuchi kinetic models. Conclusion: The present study results emphasized that LLCPNPs could be proposed as an unrivaled carrier to promote the bioavailability, stability and shelf-life of nutraceutical and biopharmaceutical formulations containing bioactive peptides.